QUALITY OF LIFE IN THALASSEMIA PATIENTS WITH IRON OVERLOAD AT THE NATIONAL INSTITUTE OF HEMATOLOGY AND BLOOD TRANSFUSION IN 2022 (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the quality of life of Thalassemia patients with iron overload at the NationalInstitute of Hematology and Blood Transfusion.Methods: cross-sectional descriptive study was conducted on 388 patients treated at the NationalInstitute of Hematology and Blood Transfusion.Results: PCS 38.9±18.4; MCS 40.2±19.7; HRQoL score 39.6±17.2. HRQoL in men (46.5±16,8)higher than in women (37.5±15,7); urban (46.2±16.8) higher than in rural mountainous (39.2±17.2);patients with moderate iron overload (42.7±17.4) was higher than the severe (38.2±19.2).Conclusion: The patient’s quality of life was low with 39.4% poor and 60.6% moderate or higher.Quality of life varies by age, gender, place of residence, iron overload status and duration of treatment.
Keywords: Quality of life (QoL); SF-36; physical health, mental health.